Biodiversity, ecology, and bionomic aspects of Anopheles mosquitoes during the dry season in southern Sumatra - DALILAH DALILAH; CHAIRIL ANWAR; DIN SYAFRUDDIN; R. IRPAN PAHLEPI; IRSAN SALEH (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Dalilah D, Anwar C, Syafruddin D, Saleh I, Pahlepi RI. 2024. Biodiversity, ecology, and bionomic aspects of Anopheles mosquitoes during the dry season in southern Sumatra. Biodiversitas 25: 1644-1654. South Sumatra and Lampung are western parts of Indonesia’s provinces that are endemic to malaria. This study aimed to determine Anopheles mosquitoes’ diversity, ecology, and biting behavior in both provinces. Understanding the diversity, ecology, and bionomy of Anopheles supports malaria elimination in endemic areas as well as surveillance of vectors in malaria-eliminated areas. The study was conducted during the dry season from June to July 2023. Mosquitoes were collected from southern Sumatra, Indonesia, i.e. Segara Kembang Village in Ogan Komering Ulu (OKU) District, South Sumatra Province, as well as Gayau and Durian Villages in Pesawaran District, Lampung Province. Adult mosquitoes were caught by human landing, resting, and cattle bait collection, while larvae were collected with dippers in the breeding habitat. A total of 4426 mosquitoes from 8 species of Anopheles were identified based on their morphology. The diversity index of Anopheles from all sample areas during this season was low (H’<1). Anopheles barbirostris s.l. and An. vagus found in habitats such as paddy fields and former fish ponds in OKU and Pesawaran District. As for abandoned shrimp ponds in Pesawaran, An. sundaicus s.l. and An. subpictus s.l. were the dominant ones. Mosquito An. sundaicus s.l seems to have a greater tendency to bite humans, whereas An. subpictus s.l was generally zoophilic. An. vagus was always present in all collection methods in all villages, with the greatest abundance in OKU. The finding indicates An. vagus appears to be the most variable in the behavior of all captured mosquitoes; therefore, in the future, it may be able to act as a major vector if transmission is not prevented.